Corrigendum to “The role of teachers in curriculum development character-based Arabic learning in Madrasah Ibtidaiyah” - Rusdy Iskandar; Andi Prastowo (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
In the original published version of this article, the authors incorrectly added “UIN Sunan Kalijaga, Yogyakarta, Indonesia” and email (21204082015@student.uin-suka.ac.id) as an affiliation and email address for Rusdy Iskandar. The affiliations have now been corrected. The authors apologize for the error. The PDF versions of the article have been updated to correct the errors.